Sistem pengurusan inventori dan tempahan bersepadu berasaskan web : makmal jabatan pendidikan sains dan matematik - Mahmod, Mohd. Khairi (2006)
Every organization possesses its own method in managing and controlling the inventory system. A study over inventory management has been carrying out at Department of Science and Mathematic Education Lab (JPSM), Faculty of Education in order to develop a Web Based Inventory and Order System. This system therefore will resolve and replace the current system process besides increasing the inventory management system in order to produce an effective and efficient system. Apart from that, an approach of Circular Model will be presented as methodology. In particular, this system will be developed using Macromedia Dreamweaver MX, Microsoft Internet Explorer, Active Server Pages (ASP), Microsoft Internet Information Services (IIS), and Microsoft Access 2003 as the database. This system also integrated with Periodic Review System Model for inventory control. In conclusion, this system development is wished will solve the problems faced by the organization besides providing a few information as a basic guideline to inventory management.